2016
DOI: 10.1186/s40323-016-0083-7
|View full text |Cite
|
Sign up to set email alerts
|

Static fracture and modal analysis simulation of a gas turbine compressor blade and bladed disk system

Abstract: This paper presents a methodology for conducting a 3-D static fracture analysis with applications to a gas turbine compressor blade. An open crack model is considered in the study and crack-tip driving parameters are estimated by using 3-D singular crack-tip elements in ANSYS . The static fracture analysis is verified with a special purpose fracture code (FRANC3D). Once the crack front is perfectly defined and validated, a free vibration study is conducted by analyzing the natural frequencies and modeshapes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The propagation process of the crack initiation to the bottom of the specimen in the symmetrical loading model of Group-A was selected for quantitative analysis. Studies [32] have shown that the solution is more accurate when the median extension defaults to 15%~20% of the crack radius and the template radius defaults to 10% of the crack radius. In this section, the median extension is set to 15% of the crack radius, which is 0.75 mm.…”
Section: Crack Growth Ratementioning
confidence: 99%
“…The propagation process of the crack initiation to the bottom of the specimen in the symmetrical loading model of Group-A was selected for quantitative analysis. Studies [32] have shown that the solution is more accurate when the median extension defaults to 15%~20% of the crack radius and the template radius defaults to 10% of the crack radius. In this section, the median extension is set to 15% of the crack radius, which is 0.75 mm.…”
Section: Crack Growth Ratementioning
confidence: 99%
“…Finite element analysis is used extensively to simulate rotating machinery (Rao, 2010;Kumar, 2011). Fernandes et al, (2016) presented a finite element model for performing a 3-D static fracture analysis of a gas turbine compressor blade in ANSYS software. Virdi et al, (2017) designed and analyzed an impeller in Catia and ANSYS, respectively.…”
Section: Introduction Girişmentioning
confidence: 99%
“…Blades are important components in power and energy equipment. The formability of material and the complexity of structural shape are two key factors during the design and manufacture process of blades . In practical engineering, blades are often manufactured as smooth curved surface shapes to satisfy the performance requirements for harsh environment.…”
Section: Introductionmentioning
confidence: 99%
“…The formability of material and the complexity of structural shape are two key factors during the design and manufacture process of blades. [4][5][6] In practical engineering, blades are often manufactured as smooth curved surface shapes to satisfy the performance requirements for harsh environment. These smooth curved surface shapes can generate wake flow field, secondary flow, and boundary layer separation.…”
Section: Introductionmentioning
confidence: 99%